Using a Storybook and the Four Resources Model to Foster Critical Literacy in an English as a Foreign Language Classroom - Yayu Sri Rahayu; Agus Kusnandar; Wintarsih Wintarsih; Rizki Widiastuti (Research Collaboration Community (RCC), 2024)
The ideology and social-political viewpoints of the author have an impact on their texts. Students should thus assess their reading and writing assignments from several angles and avoid taking any material at face value. However, there is still a lack of literacy practice in the EFL environment that goes beyond breaking down linguistic elements and comprehending the surface material of the texts. As a result, educators should switch from conventional literacy to critical literacy. Beyond just decoding words, critical literacy interprets them in light of their context to conclude the social, political, and ideological viewpoints expressed in the text. This research aims to determine if using a storybook and the four resources model of critical literacy may help first- semester students in the English Language Education Study Program at Universitas Bale Bandung practice critical literacy. The four resources model suggested by Luke and Freebody (1999) served as the foundation for the text discussions. Focus group interviews, classroom observations, and notebooks they kept while researching a tale were all used to gather the data. The results demonstrated that including an account and four resources help pupils strengthen their critical thinking skills. Through breaking codes exercises, discussion of the storybook during the meaning-making stage, comprehension of the story's structural elements and social function during the text-use phase, and critical discussion of the storybook, the students could identify the writer's language choice and challenge social norms. Despite its drawbacks and limitations, this research shows that critical literacy practice is feasible in EFL contexts, particularly in reading classroom.